Comparison of Fatigue Life Behavior between Two Different Composite Materials Subjected to Shot Peening at Different Times - Al-Khazraji, Ahmed N.; M. Shareef, Mahdi N. (Al-Khwarizmi Engineering Journal, 2014)
This paper investigated the fatigue life behavior of two composite materials subjected to different times of shot peening (2, 4 and 6 min).The first material prepared from unsaturated polyester with E-glass reinforcement by 33% volume fraction. While, the second one was prepared from unsaturated polyester with aluminum powder by2.5% volume fraction. The experimental results showed that the improvement in endurance limit was obtained (for the first material) at 2, 4 and 6 min shot peening times where the percentage of maximum improvement was 25% at shot peening time of 6 min. While, the endurance limit of the second material decreased at shot peening times of 2, 4 and 6 min where the percentage of maximum reduction was 29 % at shot peening time of 6 min. The verification of experimental results was done using ANSYS.14 workbench with a good agreement in behavior between the experimental and numerical.